Estimates of genetic and phenotypic parameters for reproductive traits in Iranian native Kordi sheep - Saghi, Davoud Ali; Shahdadi, Ali Reza (Acta Scientiarum. Animal Sciences, 2017)
The data set for estimation of genetic and phenotypic parameters of reproductive traits in Kordi sheep were collected from 1996 to 2013. The reproductive traits included age at first lambing (AFL), number of lambs born (NLB/EL) and weaned (NLW/EL) per ewe in each lambing, total weight of lambs born (TWLB/EL) and weaned (TWLW/EL) per ewe in each lambing, total number of lambs born (TNLB) and weaned (TNLW) per ewe, total weight of lambs born (TWLB) and weaned (TWLW) per ewe. The genetic parameters were estimated through restricted maximum likelihood method using WOMBAT. The effects of environmental factors (year of lambing, type of birth, maternal age at lambing) on all reproductive traits were significant (p < 0.01). Direct heritability, maternal heritability and the ratio of maternal permanent environmental variance to phenotypic variance for reproductive traits were estimated in the range from 0.07 to 0.18, 0.03 to 0.08 and 0.01 to 0.03, respectively. Genetic and phenotypic correlations between reproductive traits were estimated to be positive and within the range of 0.09 to 0.96 and 0.02 to 0.29, respectively. The results suggest that selection based on number of lambs born per ewe can be more effective than other traits in improving reproductive performance in Kordi ewes.